A STUDY OF THE ROLE OF SOCIAL INEQUALITY IN PROMOTING SOCIAL CHANGE - Ved Prakash (International Journal of Multidisciplinary Research and Studies, 2021)
In recent years, there has been a growing concern about the rising income inequalities, with particularly stark rises in inequality in the United States and also a substantial widening of the income gap in Europe. The United States has seen particularly stark rises in inequality, and Europe has seen a substantial widening of the income gap. Because of this, an increasing number of people are speaking out against the current tendencies, and they do not approve of them. The importance of the widening of economic inequality has not only garnered the attention of politicians and scholars, but it is also frequently debated on the streets of the globe today, with the movement known as "Occupy Wall Street" being the most well-known example of such rallies. This movement and its frequently referenced motto, "We are the 99%," alludes explicitly to a rising disparity in the distribution of wealth (see, for example, the coverage of the movement by the New York Times in 2011, as well as the web blog entitled "We are the 99%," published in 2012). This disparity in wealth distribution has been growing over the past several decades. An OECD research that was published not too long ago focused on the recent growth in income inequality that has been noticed across the member states of the EU.